Duck rice stop hall business plan - Mega Wati Ayu Ningsih; Suwandi Suwandi (Sean Institute, 2024)
The duck rice shelter business plan is a new business plan that will be started in the North Jakarta area. With a healthy and fast food proposition, the main activity is preparing the main food menu, namely duck and free-range chicken as a side menu. This duck rice shelter business plan will use a descriptive analysis method which will be prepared based on information obtained from field surveys and a business model created based on information from existing duck businesses, especially those located in Jakarta, using the Empathy Map and Business approach. Canvas Models. The assessment of the feasibility of this duck rice shelter business plan will be carried out using the financial analysis parameters of payback period, IRR and NPV. The results of the research analysis and discussion conclude: 1. The duck and free-range chicken menu is a healthy food high in cholesterol; 2. In terms of business feasibility, the financial flow projection for 2 years shows a payback period of 1 year, a positive NPV of IDR 12,798,743,- and an IRR of 30.36% which is greater than the minimum attractive rate of return (MARR), which is 10%.